Composite fluorescent glass film as well as preparation method and application thereof
By using a composite fluorescent glass film of a specific composition in the white LED, the problem of insufficient color rendering index of white LEDs in the prior art is solved, and a white light effect with a high color rendering index and a color temperature of less than 6000K is achieved.
Patent Information
- Application Number
- CN202411752750.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the color rendering index of white LEDs still needs to be improved, especially in the cold white light range, which is not sufficient to meet the needs of certain applications.
A composite fluorescent glass film is used, and its composition includes orange phosphor, cyan phosphor and glass powder. Through a specific mass ratio and composition, white light with a color temperature of less than 6000K is generated under excitation.
The color rendering index of white light generated under the excitation of blue light sources is achieved to reach 93.4, meeting the demand for color temperature less than 6000K, and improving the color uniformity of light.
Smart Images

Figure CN119612960A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite fluorescent glass film and a preparation method thereof, and in particular to a composite fluorescent glass film which generates white light under the excitation of a blue light source and a preparation method and application thereof. Background Art
[0002] Generally, light with a color temperature above 6000K is called cold white light. Since the proportion of blue light is relatively high, the light emitted is bluish, giving people a "cold" feeling, so it is called cold white light. Cold white light is more dazzling and is usually used for decoration and local lighting. Light with a color temperature less than 6000K is more natural and can be used for home lighting.
[0003] CN107785476A discloses a fluorescent glass film for white light LED and its preparation method, comprising a first glass substrate coated with an ITO conductive film, a second glass substrate and a phosphor layer sandwiched between the first glass substrate and the second glass substrate, wherein the ITO conductive film is an Sn-doped ITO film, and the phosphor layer comprises a mixture of Ce:YAG yellow phosphor, green phosphor and red phosphor, wherein the green phosphor is selected from lead halide cesium green phosphor, Ce:LuAG green phosphor or Ce:GaAG green phosphor, and the red phosphor is selected from silicate red phosphor or nitride red phosphor. Its color temperature is between 4000 and 5000K, and the color rendering index is 89.1. The composition is complex and the color rendering index still needs to be improved.
[0004] CN108455846A discloses a fluorescent glass with composite fluorescent powder and a preparation method thereof, wherein the composite fluorescent powders are green fluorescent powder and red fluorescent powder, and the amount of the composite fluorescent powder added is 1-10% of the weight of the matrix glass powder. In this method, after being packaged into a white light LED device, the color rendering index is still low.
[0005] CN112760095A discloses a fluorescent material for a fluorescent conversion type white light laser light source and a preparation method thereof. The fluorescent material comprises a YAG single crystal substrate and a fluorescent glass film layer, wherein the fluorescent glass film layer is a thin film layer of a mixture of red fluorescent powder and low melting point glass powder; the YAG single crystal substrate is prepared by a Czochralski method, and one side is polished and one side is ground rough; the fluorescent glass film layer is printed on the rough surface of the YAG single crystal by a screen printing process, and then heat treated. The color rendering index of the fluorescent material as a fluorescent conversion material for laser white light still needs to be improved.
[0006] CN114836195A discloses a preparation method and application of a fluorescent composite glass film, including a blue laser diode, a composite fluorescent glass film, a blue light transmission film, a sapphire substrate, and a heat sink; in the composite fluorescent glass film, fluorescent powder: glass powder: thermal conductive filler are mixed in a mass fraction ratio of 3:2:5; the thermal conductive filler is a mixture of two to three of the three thermal conductive materials of Al2O3, AlN, and BN; the blue light generated by the blue laser diode excites the composite fluorescent glass film to generate yellow light, and the yellow light is mixed with the blue laser to form uniform white light. The white light formed in this method is cold white light, with a color temperature above 6000K, and the color rendering index still needs to be improved. Summary of the invention
[0007] In view of this, one object of the present invention is to provide a composite fluorescent glass film, which generates white light with a color temperature less than 6000K under the excitation of a blue light source, and the color rendering index of the white light is relatively high. Another object of the present invention is to provide a method for preparing the composite fluorescent glass film as described above. Another object of the present invention is to provide an application of the composite fluorescent glass film as described above. The present invention adopts the following technical solutions to achieve the above objects.
[0008] In one aspect, the present invention provides a composite fluorescent glass film having a composition as shown in formula (1):
[0009] A·B·Glass powder (1);
[0010] A is orange phosphor, B is cyan phosphor;
[0011] The mass ratio of A to B is 2 to 6:1; the mass ratio of the sum of A and B to the mass of the glass powder is 6.2 to 7.2:3;
[0012] Among them, the composition of A is Lu 3-x Ce x Mg2AlSi2O 12 ; x represents the molar fraction of Ce element, 0.01≤x≤0.1.
[0013] According to the composite fluorescent glass film of the present invention, preferably, in formula (1), the maximum emission wavelength of A is 595-610 nm, and the maximum emission wavelength of B is 490-510 nm.
[0014] According to the composite fluorescent glass film of the present invention, preferably, in formula (1), the composition of B is (Ba, Sr)Si2O2N2:Eu.
[0015] According to the composite fluorescent glass film of the present invention, preferably, in formula (1), the composition of the glass powder is SiO2·B2O3·ZnO, and B in the glass powder is boron element.
[0016] On the other hand, the present invention also provides a method for preparing the composite fluorescent glass film as described above, comprising the following steps:
[0017] 1) Mixing two kinds of phosphors A and B and glass powder according to a mass ratio to obtain a premix;
[0018] 2) mixing the premix with the organic rubber to obtain a mixture;
[0019] 3) coating the mixture on a substrate and curing it to obtain a precursor;
[0020] 4) Calcine the precursor to obtain a composite fluorescent glass film.
[0021] According to the preparation method of the present invention, preferably, in step 2), the organic sizing material comprises terpineol, diethylene glycol butyl ether acetate and ethyl cellulose, and the mass ratio of the three is 4.5-5.5:1-2.1:1.
[0022] According to the preparation method of the present invention, preferably, in step 2), the mass volume ratio of the premix to the organic rubber is 1-5 g:1 mL.
[0023] According to the preparation method of the present invention, preferably, in step 3), the mixture is coated on a substrate and vacuum dried and cured at 100-130° C. for 5-30 min; the substrate is a sapphire substrate.
[0024] According to the preparation method of the present invention, preferably, the calcination temperature is 700-800° C. and the calcination time is 5-15 min.
[0025] On the other hand, the present invention also provides the use of the composite fluorescent glass film as described above in the preparation of a white light LED light source, wherein the composite fluorescent glass film generates white light with a color temperature less than 6000K under the excitation of a blue light source, and the color rendering index Ra of the white light reaches 93.4.
[0026] The composite fluorescent glass film of the present invention can generate white light with a color temperature less than 6000 K under the excitation of a blue light source. Furthermore, the fluorescent glass film of the present invention has uniform light color and a high color rendering index Ra, which reaches 93.4. The preparation method of the present invention is simple and has good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD result diagram of the composite fluorescent glass film obtained in Example 1.
[0028] Figure 2 This is a scanning electron microscope image of the composite fluorescent glass film obtained in Example 1.
[0029] Figure 3 This is the element distribution image of the composite fluorescent glass film obtained in Example 1.
[0030] Figure 4 The excitation spectrum and emission spectrum of the composite fluorescent glass film obtained in Example 1, wherein (a) is the excitation spectrum and (b) is the emission spectrum.
[0031] Figure 5 This is the electroluminescence spectrum obtained in Application Example 1.
[0032] Figure 6 This is the CIE coordinate diagram obtained from Application Example 1. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0034] <Composite fluorescent glass film>
[0035] The composite fluorescent glass film of the present invention can generate white light under the excitation of a blue light source. The composite fluorescent glass film has a composition as shown in formula (1):
[0036] A·B·Glass powder (1);
[0037] In formula (1), A is orange phosphor, and B is cyan phosphor.
[0038] The mass ratio of A to B is 2 to 6:1, preferably 2 to 5:1, more preferably 2 to 4:1, and further preferably 2 to 3:1. The luminescent materials in the composite fluorescent glass film of the present invention can better interact with each other, thereby improving the luminous intensity and color rendering index of white light.
[0039] In the present invention, the composition of A is Lu 3-x Ce x Mg2AlSi2O 12 ; x represents the molar fraction of Ce element, 0.01≤x≤0.1, preferably, 0.02≤x≤0.09, more preferably, 0.03≤x≤0.08, further preferably, 0.04≤x≤0.07, for example, x is 0.04, 0.05, 0.06, 0.07. Wherein, Lu is lutetium element, Ce is cerium element, Mg is magnesium element, Al is aluminum element, Si is silicon element, and O is oxygen element. The maximum emission wavelength of A (can be abbreviated as λ A ) is 595 to 610 nm. Preferably, 595 ≤ λ A ≤600nm. This is beneficial to improve the luminous intensity and color rendering index of the composite fluorescent glass film.
[0040] A in the present invention can be prepared by a high-temperature solid phase method. In certain specific embodiments, the raw materials are weighed and ground uniformly according to the stoichiometric ratio, placed in a tube furnace, sintered at 1300-1450°C for 3-5 hours under a reducing atmosphere, and then cooled to room temperature. The sintering temperature is preferably 1350-1450°C, more preferably 1400-1420°C. The sintering time is preferably 4-5 hours, more preferably 4-4.5 hours.
[0041] The maximum emission wavelength of B in formula (1) (can be abbreviated as λ B ) is 490 to 510 nm. Preferably, 495 ≤ λ B ≤505nm. In some specific embodiments, the maximum emission wavelength of B is 495nm. According to a specific embodiment of the present invention, the composition of B is: (Ba, Sr) Si2O2N2: Eu. It can be commercially available. Among them, Ba is barium, Sr is strontium, Si is silicon, O is oxygen, N is nitrogen, and Eu is europium. This is conducive to improving the luminous intensity and color rendering index of the composite fluorescent glass film.
[0042] In the present invention, the ratio of the sum of the mass of A and B to the mass of the glass powder is 6.2-7.2:3, preferably 6.5-7.2:3, more preferably 6.8-7.2:3, for example 7:3. The composite fluorescent glass film formed in this way can form white light with a color temperature of less than 6000K and a color rendering index greater than 90 under the excitation of a blue light source. If the content of the two fluorescent powders is too high or too low, good white light cannot be formed.
[0043] In the present invention, the specific composition and source of the glass powder are not particularly limited, and lead-free borosilicate glass powder is preferred. In certain specific embodiments, the glass powder may be composed of SiO2·B2O3·CaO, which can be commercially available. In the composition of the glass powder, B refers to the boron element, Ca is the calcium element, Si is the silicon element, and O is the oxygen element.
[0044] In the present invention, the thickness of the composite fluorescent glass film is 30 μm or more, preferably 50 to 150 μm, more preferably 60 to 100 μm, and even more preferably 60 to 80 μm.
[0045] In the present invention, the composite fluorescent glass film generates white light with a color temperature less than 6000K under the excitation of a blue light source, and has a high color rendering index. The excitation wavelength range of the blue light excitation light source is 440 to 470 nm. Preferably, the excitation wavelength is 440 to 450 nm. The blue light can excite the fluorescent powder to the maximum extent after passing through the composite fluorescent glass film.
[0046] <Preparation method>
[0047] The method for preparing the composite fluorescent glass film of the present invention comprises the following steps:
[0048] (1) Premixing step; (2) Mixing step; (3) Coating and curing step; (4) Firing step. These are described in detail below.
[0049] Premixing step
[0050] The phosphors A and B and the glass powder are mixed according to a mass ratio to obtain a premix. The mass ratio of the phosphors A and B and the mass ratio of the glass powder to the two phosphors are as described above and will not be described in detail here.
[0051] In the present invention, during premixing, the two phosphors A and B and the glass powder can be ground and mixed uniformly.
[0052] Mixing Steps
[0053] The premix is mixed with the organic rubber to obtain a mixture.
[0054] In the present invention, the organic sizing material includes terpineol, diethylene glycol butyl ether acetate and ethyl cellulose, and the mass ratio of the three is 4.5-5.5:1-2.1:1, preferably 4.8-5.5:1-1.7:1, and more preferably 5.0-5.5:1-1.5:1.
[0055] In certain specific embodiments, the organic sizing material consists only of terpineol, diethylene glycol butyl ether acetate and ethyl cellulose, and the mass ratio of the three is 4.5-5.5:1-2.1:1.
[0056] In the present invention, the organic sizing material is prepared by the following steps: terpineol, diethylene glycol butyl ether acetate and ethyl cellulose are mixed, and stirred at 50-65° C. and 500-700 rpm for 3-5 hours.
[0057] In the present invention, the mass volume ratio of the premix to the organic sizing agent is 1-5 g:1 mL, preferably 1-4 g:1 mL, and more preferably 1-3 g:1 mL, which is conducive to forming a uniform composite fluorescent glass film.
[0058] Coating and curing steps
[0059] The mixed material is coated on a substrate and cured to obtain a precursor.
[0060] In the present invention, the substrate is a sapphire substrate, specifically, the substrate is a sapphire substrate. Such a substrate has high thermal conductivity, so that the composite fluorescent glass film has strong thermal conductivity.
[0061] According to one embodiment of the present invention, the mixed material is coated on a substrate and vacuum dried and cured at 100 to 130° C. for 5 to 30 minutes.
[0062] The curing temperature can be 100-130° C., preferably 105-125° C., more preferably 110-120° C. The curing time (i.e., curing molding time) can be 5-30 minutes, preferably 7-25 minutes, more preferably 8-20 minutes. This is conducive to improving the luminous intensity and color rendering index of the composite fluorescent glass film.
[0063] Calcination steps
[0064] The precursor is calcined to obtain a composite fluorescent glass film.
[0065] In the present invention, the calcination temperature can be 700-800°C, preferably 700-780°C, and more preferably 700-720°C. The heating rate during calcination can be 5-10°C / min, preferably 6-7°C / min. The calcination time can be 5-15min, preferably 6-12min, and more preferably 8-10min. This is conducive to improving the luminous intensity and color rendering index of the composite fluorescent glass film.
[0066] The present invention finds that calcination allows the composite fluorescent glass film to be formed, the organic glue to volatilize, and the luminescent properties of the mixed fluorescent powder to be maintained; if the time is too short, the organic glue will not volatilize completely, affecting the luminescent properties of the composite fluorescent glass film; if the time is too long, the luminescent properties of the fluorescent powder are likely to be destroyed, thereby affecting the lighting and display of the composite fluorescent glass film device.
[0067] <Application>
[0068] The present invention also provides the use of the composite fluorescent glass film as described above in the preparation of a white light LED light source, wherein the composite fluorescent glass film generates white light with a color temperature less than 6000 K under the excitation of a blue light source. For example, white light with a color temperature of 5710 K can be generated. The color rendering index Ra of the generated white light can reach 93.4.
[0069] Here is the test method:
[0070] XRD determination: The X'Pert PRO XRD powder diffractometer produced by Panalytical was used for the test.
[0071] Scanning electron microscopy measurement: The test was conducted using a Sigma500 field emission scanning electron microscope produced by ZEISS.
[0072] Fluorescence spectrometry: The test was conducted using the FSL1000 steady-state / transient fluorescence spectrometer produced by Edinburgh Instruments.
[0073] Electroluminescence spectrum measurement: The test was conducted using the PCE-2000A photoelectric color comprehensive test system produced by Hangzhou Yuanfang Optoelectronic Information Co., Ltd.
[0074] The following is an explanation of the sources of some raw materials: Cyan phosphor (Ba, Sr)Si2O2N2:Eu, which can also be written as (Ba, Sr)Si2O2N2:Eu 2+ , purchased from Youyan Rare Earth New Materials Co., Ltd. Glass powder was purchased from Guangzhou Dinghua Nano New Materials. Orange phosphor Lu 3-x Ce x Mg2AlSi2O 12 (x=0.06) is prepared by a high-temperature solid phase method. The raw materials are weighed and ground evenly according to the stoichiometric ratio, placed in a tubular furnace, sintered at 1400°C for 4 hours in a 5vol% H2+95vol% N2 reducing atmosphere, and naturally cooled to room temperature.
[0075] Example 1
[0076] According to the formula in Table 1, two phosphors A and B are mixed with glass powder to obtain a premix. A is orange phosphor and B is cyan phosphor. The composition of A is Lu 3-x Ce x Mg2AlSi2O 12 , x = 0.06. The composition of B is (Ba, Sr)Si2O2N2:Eu. The composition of the glass powder is SiO2·B2O3·CaO.
[0077] Terpineol, diethylene glycol butyl ether acetate and ethyl cellulose were mixed in a mass ratio of 5:1:1, and stirred at 50° C. and 600 rpm for 3 hours to obtain an organic sizing material.
[0078] The premixed material and the organic rubber material are mixed at a mixing ratio of 1 g:1 mL by mass volume to obtain a mixed material.
[0079] The mixture was coated on a sapphire substrate, and then placed in a vacuum drying oven, vacuum dried and solidified at 120° C. to obtain a precursor. The precursor was then calcined at 700° C. for 10 min to obtain a composite fluorescent glass film having a thickness of 80 μm.
[0080] The XRD results of the composite fluorescent glass film obtained in this example are shown in Figure 1 , Figure 1 In the figure, the black line is the diffraction peak of the blank sapphire sheet, and the orange line is the diffraction peak of the composite fluorescent glass film. Figure 2 , there is no obvious crack on the film surface. Element distribution image is shown in Figure 3 ,Depend on Figure 3 It can be seen that the elements in the film are distributed relatively evenly. The excitation spectrum and emission spectrum are shown in Figure 4 , where (a) is the excitation spectrum and (b) is the emission spectrum. Figure 4 It can be seen that the excitation peak of the film covers 440-500nm, and the emission peak covers an ultra-wide emission range of 480-780nm.
[0081] Table 1
[0082] Raw material types Orange phosphor A Cyan phosphor B Glass powder Raw material dosage 4.7 parts by weight 2.3 parts by weight 3 parts by weight
[0083] Application Example 1
[0084] The composite fluorescent glass film obtained in Example 1 was encapsulated on a blue LED chip to prepare a full-spectrum white LED device. Under the excitation of the blue LED chip, the composite fluorescent glass film exhibited white light emission, and full-spectrum white LED lighting could be achieved.
[0085] like Figure 5 and Figure 6 As shown, by coupling the composite fluorescent glass film of Example 1 with a blue LED chip (wavelength of 440nm), high-quality white light is obtained, the color rendering index Ra of the white light is 93.4, the correlated color temperature CCT=5710K, and the color coordinates (x, y) are (0.3274, 0.3565). It can be seen that the composite fluorescent glass film of the present invention can achieve ultra-wide spectrum coverage, thereby obtaining white light with high color rendering index and color temperature less than 6000K.
[0086] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A composite fluorescent glass film, characterized in that: As shown in formula (1) composition: A·B·Glass powder (1); A is orange phosphor, B is cyan phosphor; The mass ratio of A to B is 2 to 6:1; the mass ratio of the sum of A and B to the mass of the glass powder is 6.2 to 7.2:3; Among them, the composition of A is Lu 3-x Ce x Mg2AlSi2O 12 ; x represents the molar fraction of Ce element, 0.01≤x≤0.
1.
2. The composite fluorescent glass film according to claim 1, characterized in that: In formula (1), the maximum emission wavelength of A is 595-610 nm, and the maximum emission wavelength of B is 490-510 nm.
3. The composite fluorescent glass film according to claim 1, characterized in that: In formula (1), the composition of B is (Ba, Sr)Si2O2N2:Eu.
4. The composite fluorescent glass film according to claim 1, characterized in that: In formula (1), the composition of the glass powder is SiO2·B2O3·ZnO, and B in the glass powder is boron element.
5. The method for preparing the composite fluorescent glass film according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Mixing two kinds of phosphors A and B and glass powder according to a mass ratio to obtain a premix; 2) mixing the premix with the organic rubber to obtain a mixture; 3) coating the mixture on a substrate and curing it to obtain a precursor; 4) Calcine the precursor to obtain a composite fluorescent glass film.
6. The preparation method according to claim 5, characterized in that: In step 2), the organic sizing material comprises terpineol, diethylene glycol butyl ether acetate and ethyl cellulose, and the mass ratio of the three is 4.5-5.5:1-2.1:
1.
7. The preparation method according to claim 5, characterized in that: In step 2), the mass volume ratio of the premix to the organic rubber is 1-5 g:1 mL.
8. The preparation method according to claim 5, characterized in that: In step 3), the mixture is coated on a substrate and vacuum dried and cured at 100-130° C. for 5-30 minutes; the substrate is a sapphire substrate.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The calcination temperature is 700-800°C, and the calcination time is 5-15 minutes.
10. Use of the composite fluorescent glass film according to any one of claims 1 to 4 in preparing a white light LED light source, characterized in that: The composite fluorescent glass film generates white light with a color temperature less than 6000K under the excitation of a blue light source, and the color rendering index Ra of the white light reaches 93.4.
Citation Information
Patent Citations
Fluorescent glass film for white light LED, and preparation method thereof
CN107785476A
Fluorescence glass of composite fluorescent powder as well as preparation method and application thereof
CN108455846A
Fluorescent material for high-color-rendering fluorescence conversion type white laser light source and preparation method thereof
CN112760095A